B-Cell Receptor-Associated Protein 31 Negatively Regulates the Expression of Monoamine Oxidase A Via R1 - Jia, Cong-cong; Li, Guoxun; Jiang, Rui; Liu, Xia; Yuan, Qing; Le, Weidong; Hou, Yue; Wang, Bing (Frontiers in Molecular Biosciences, 2020)
B-cell receptor associated protein 31 (Bap31) is a three trans-membrane protein of the endoplasmic reticulum (ER). Patients that loss the function of Bap31 suffered from X-linked syndrome, such as motor and intellectual disabilities, dystonia and sensorineural deafness. However, the underlying mechanism of Bap31 on X-linked syndrome remains unclear. Here, we found that a total of 21 proteins (9 up- and 12 down-regulated proteins) related with X-linked syndrome were screened from shRNA-Bap31 transfected cells with the isobaric tags for relative and absolute quantification (iTRAQ) technique. One gene with the greatest change trend, monoamine oxidase A (MAOA), was identified. MAOA expression was up-regulated by Bap31 knockdown. However, Bap31 did not affect the ubiquitination degradation of MAOA protein . Of note, Bap31 selectively regulated the expression of cell division cycle associated 7 like (R1/RAM2/CDCA7L/JPO2, a transcriptional repressor of MAOA) and the binding activity of R1 with MAOA promoter, thereby affecting MAOA expression. This study demonstrates the molecular mechanisms of Bap31 in MAOA via R1, and supports the potential function of Bap31 on X linked syndrome.